Juego con el concepto de “obra orgánica” en 5 metros de poemas, de Carlos Oquendo de Amat - León Mango, Liz Fiorella (2019)
Through the analysis of 5 metros de poemas, by Carlos Oquendo de Amat, it is proposed to demonstrate an attempt of emancipation of Peruvian poetry with respect to the traditional formal values that embodied the ideas of perfection and “artistic progress”. We believe that the poet, based on an expressive poetic and the play, problematized the concept of “organic book” through two playful experiments: a) the material fragmentation of the work of art as if it were a toy; b) the mixture of diverse artistic styles included in a same level as if they were pieces of game uncoupled from history and individualities.